Docência na educação infantil: uma voz masculina numa “profissão feminina” - MIRANDA, Anderson de Jesus de Sousa (2019)
The teaching and gender research brings reflections and discussions, thus showing the presence and resistance of the male professional in teaching with young children. The theme seeks to analyze gender resistance in the teaching of Early Childhood Education in the Municipal School of Early Childhood Education and Fundamental Education in the Municipality of Abaetetuba / PA. Questioning the reason why the presence of male teachers is much smaller than the female in the Early Childhood Education, what are the challenges faced by this professional in the classroom and which teaching should be performed by both men and women? From this issue, the problem arose to understand why the presence of men in teaching children is much smaller than women, and what challenges faced by this professional in the classroom, reflecting that teaching in Early Childhood Education should be both male and female. The research carried out had the objective to rethink the masculine activity in the Infantile Education and its professional activity showing that teachers (men) can act in the infantile teaching. Identifying gender relations and how they influence the insertion and permanence of the teacher as a teacher, what challenges this professional faces in the classroom since it is a predominantly female space and analyze the human relationship between teacher / student, student / teacher, teachers / school, school / teachers, teacher / family and family / teacher in the teaching of Early Childhood Education. According to Louro (1997), Oliveira (2005), gender relations are relations of power, always going to have conflicts, but can not promote inequalities, exclusions in school, always seeking reflection about the power relationship existing in teaching young children. For this study, a case study with qualitative approach, data collection, application of a semi-structured questionnaire and observation in the locus of the research were carried out. Our analysis considers that child teaching should be exercised by both male and female teachers, making gender plurality present in the classroom, removing any type of gender bias and exclusion in schools.